2018
DOI: 10.1002/pds.4614
|View full text |Cite
|
Sign up to set email alerts
|

What is the quality of drug safety information for patients: An analysis of REMS educational materials

Abstract: Currently approved REMS patient materials fell short in terms of recommended reading level, and over half did not meet recommended standards for actionability. Developers of these materials should apply plain language principles when design these materials to improve their readability and to assess both understandability and actionability in order to increase the effectiveness when distributed to patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Fact sheets, handbooks/brochures/booklets are more dispersed across readability indices potentially highlighting the variability in the consideration applied to these materials in terms of their accessibility to low health literacy population. Compared to print chronic kidney disease materials and drug safety information for patients, both of which averaged a ninth‐grade reading level, presently identified deprescribing patient education materials were much more difficult to read with at least an average 10th‐grade reading level. However, due to the limitation of readability indices which consider a limited set of parameters and are not always indicative of ease of comprehension, readability indices form only a fraction of the picture so should be interpreted cautiously, particularly given that different readability measures can provide very different results …”
Section: Discussionmentioning
confidence: 99%
“…Fact sheets, handbooks/brochures/booklets are more dispersed across readability indices potentially highlighting the variability in the consideration applied to these materials in terms of their accessibility to low health literacy population. Compared to print chronic kidney disease materials and drug safety information for patients, both of which averaged a ninth‐grade reading level, presently identified deprescribing patient education materials were much more difficult to read with at least an average 10th‐grade reading level. However, due to the limitation of readability indices which consider a limited set of parameters and are not always indicative of ease of comprehension, readability indices form only a fraction of the picture so should be interpreted cautiously, particularly given that different readability measures can provide very different results …”
Section: Discussionmentioning
confidence: 99%
“…Our study has provided a broad overview of patient attitudes to medicine safety information. Much of the research in this field to date has had a single research area focus, for example consumer use of the package insert, [ 7,9,14 ] consumer attitudes towards pharmacist‐delivered health services and health information [ 1 ] or the public perception of the pharmaceutical industry. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Package information leaflets may not provide information on medication side effects at an appropriately accessible level. [ 9,22–25 ] Indeed, we may require a tailored approach to information dissemination that takes into account the nature of the side effect, its likelihood and the patient demographics. [ 14,16,25–27 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational theory suggests that presenting congruent information in multiple formats can help to increase comprehension. 25 Some studies suggest that pictures can enhance patients' understanding of the effect of medication treatment 53 and self-management recommendations. 54 In our study, we found that patients preferred to use pictures showing clinical manifestations to judge whether they had the same symptoms, and patients, especially those with low health literacy, preferred to obtain important knowledge through cartoon stories.…”
Section: Discussionmentioning
confidence: 99%